1997
DOI: 10.1073/pnas.94.20.11019
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences of NR2 subunit composition in single recombinant N -methyl- d -aspartate receptors

Abstract: The N-methyl-D-aspartate (NMDA) receptor is a ligand-gated ion channel involved in excitatory neurotransmission, synaptic plasticity, and neuronal cell death. Two families of NMDA receptor subunits exist: the NR1 subunit (1), which is found in eight alternatively spliced isoforms (2), and the NR2 subunit, for which four subtypes have been described (NR2A-D), each one being a different gene product (3-7). Functional NR1 homomers apparently can be assembled in frog oocytes (1), whereas receptors in mammalian cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 32 publications
2
65
1
Order By: Relevance
“…However, the molecular mechanism through which activation of NMDA regulates D1 receptor trafficking and D1-mediated cAMP accumulation is not identified. In contrast, Fiorentini et al (2003) shows that coexpression of D1 and NR1/2B subunits abolished the agonist-induced D1 receptor intracellular sequestration, suggesting that NMDA receptors may modulate D1 receptor trafficking through multiple regulatory pathways dependent on the NMDA receptor subunit composition, which is consistent with previous reports that clearly have demonstrated functional differences with distinct NMDA receptor subunit compositions (Brimecombe et al, 1997;Vicini et al, 1998;Barria and Malinow, 2002). Although the study by Fiorentini et al (2003) has similarities to our study reported here, there are still some clear discrepancies.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…However, the molecular mechanism through which activation of NMDA regulates D1 receptor trafficking and D1-mediated cAMP accumulation is not identified. In contrast, Fiorentini et al (2003) shows that coexpression of D1 and NR1/2B subunits abolished the agonist-induced D1 receptor intracellular sequestration, suggesting that NMDA receptors may modulate D1 receptor trafficking through multiple regulatory pathways dependent on the NMDA receptor subunit composition, which is consistent with previous reports that clearly have demonstrated functional differences with distinct NMDA receptor subunit compositions (Brimecombe et al, 1997;Vicini et al, 1998;Barria and Malinow, 2002). Although the study by Fiorentini et al (2003) has similarities to our study reported here, there are still some clear discrepancies.…”
Section: Discussioncontrasting
confidence: 44%
“…Whereas Fiorentini and colleagues use NR2B in their studies, we have used NR2A subunits in our experiments. Several studies have demonstrated differential functional NMDA receptor properties dependent on NR2 subunit subtype composition (Krupp et al, 1996;Brimecombe et al, 1997;Sprengel et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…While the present study does not indicate whether NR2A and NR2B subunits are found in the same neurons, this is often the case (Sheng et al 1994;Flint et al 1997;Luo et al 1997;Cao et al 2000b). Furthermore, it has been reported that the addition of NR2A subunits to neurons already containing NR2B results in properties intermediate to those characterized in receptors containing only NR2A or NR2B, e.g., intermediate current duration (Flint et al 1997;Vicini et al 1998) and sensitivity to NR2B antagonists (Brimecombe et al 1997). Thus, early postnatal ACx with high levels of NR2B but low levels of NR2A should have long-duration NMDAR EPSPs, but durations should decrease proportionally with increased NR2A expression.…”
Section: Implications For Development Of Synaptic Functionmentioning
confidence: 44%
“…2, see review of [121]). The sensitivity of NMDARs to different ligands, its permeation, and block by divalent ions, kinetic properties, and interaction with intracellular proteins highly depend on their subunit composition [21,39,91]. Diheteromeric NMDARs composed of NR1/NR2A or NR1/NR2B subunits generate 'high-conductance', Mg 2+ sensitive channels permeable also to Ca 2+ ions.…”
Section: Structure and Function Of Nmda Receptorsmentioning
confidence: 99%